2013
DOI: 10.5897/ajb2013.12797
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of ten mango cultivars using simple sequences repeat (SSR) markers

Abstract: Simple sequence repeats (SSRs) which is an efficient genetic markers for comparative genome mapping can be helpful in the classification of genotypes, germplasm resource utilization and breeding programmes. Therefore, the present study was conducted to show genetic variation and investigate inter-relationship between ten mango genotypes. Twenty (20) SSR markers were tested with 10 genotypes: Kalepad, Neelum, Swarnarekha, Alphonso Rumani, Sendura, Banganapalli, Himayuddin, Mulgoa and Bangalora. The genomic DNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Shamili et al (2012) found 35-100% genetic similarity among 41 mango cultivars using 16 SSR markers. Similarly, (Kumar et al, 2013) used 20 SSR markers to study genetic relationships among 10 mango cultivars and reported similarity coefficients of 59-100%, revealing valuable levels of genetic diversity. In the present study, 75-100% genetic similarity was identified among 15 mango genotypes using 12 SSR markers.…”
Section: Discussionmentioning
confidence: 99%
“…Shamili et al (2012) found 35-100% genetic similarity among 41 mango cultivars using 16 SSR markers. Similarly, (Kumar et al, 2013) used 20 SSR markers to study genetic relationships among 10 mango cultivars and reported similarity coefficients of 59-100%, revealing valuable levels of genetic diversity. In the present study, 75-100% genetic similarity was identified among 15 mango genotypes using 12 SSR markers.…”
Section: Discussionmentioning
confidence: 99%
“…It means that microsatellites are abundant in mango relatives' genomes, essential to support variety protection efforts (Ravishankar et al 2011). Microsatellite alleles have been shown to distinguish mangoes with highly similar phenotypes (Umar et al 2013). Besides morphological and agronomic characters, heterozygosity values are also crucial for mango breeding programs (Surapaneni et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Mango production is concentrated in El-Sharkia, El-Ismailia, El-Giza, EL-Fayoum and El-Behera (Nubariya) governorates (Abourayya et al, 2012). The lack of systematic approach in naming of mango cultivars in the past has resulted in a great confusion in their nomenclature due to many synonyms and duplication of names in the absence of any rules governing nomenclature (Kumar et al, 2013;Mansour et al, 2014).…”
Section: Introductionmentioning
confidence: 99%